Application of 3D cellular automata-based analysis to chloride diffusion process in concrete bridges. (January 2023) - Al-samawi, Mohammed; Zhu, Jinsong; Rong, Wei
Abstract: Chloride-induced corrosion is one of the main reasons for degrading the serviceability and reliability of concrete bridge structures in severe environments. Consequently, a more accurate simulation of the chloride diffusion process is essential for a durable design. This paper performs a three-dimensional (3D) cellular automata (CA) model that accurately simulates chloride diffusion in concrete. The model's accuracy was investigated by comparing the results with Fick's second law (FSL), 2D-CA model, and experimental data. The 3D-CA model is improved and applied to simulate the chloride diffusion in a concrete bridge, considering the effect of multiple factors such as relative environmental humidity, variations in temperature, stresses, water-cement ratio (w/c), concrete degradation, corrosion propagation, cracking, and time. The 3D-CA model algorithms were developed using Python to accomplish this goal. The life span of the concrete bridge was assessed based on critical regions of the corrosion beginning and concrete cracking time. The 3D-CA model provides a more suitable approach to simulating chloride diffusion and predicting the initial corrosion time of reinforcement bars. It can also provide a basis for establishing a maintenance strategy with low-cost solutions for evaluating risk areas and constructing durable projects.